APLIKASI SISTEM PERANGKAT LUNAK MENGGUNAKAN ALGORITMA ANT UNTUK MENGATUR PENJADWALAN KULIAH - Saragih, Hoga; Hoendarto, Genrawan; Reza, Bobby; Setiyadi, Didik (Teknik dan Ilmu Komputer, 2012)
AntÃÂ algorithmÃÂ is one of Swarm Intellingence algorithms that can be used to solve NP-Hard problems. The scheduling of courses and lecturers which are done routinely each semester can be solved by exact methods and heuristic methods. Each institution has its own constraints in arranging the schedule. This paper discusses a case study in STMIK Widya Dharma. The type of ant algorithm used is the Rank Base Ant System suitable for scheduling based on ranking, which is the lecturersÃ¢â¬â¢ priority level. The other parametersÃÂ are subjects, space, and time. It is expected that the software being analyzed withÃÂ Ant algorithms can provide solutions to the scheduling problem.ÃÂ Keywords:ÃÂ ÃÂ  university timetable course,ÃÂ  An algorithm, ASRank